2020
DOI: 10.1159/000506456
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Bleeding Risk in Bariatric Surgeries: A Retrospective Analysis Study

Abstract: Objective: To determine the factors that influence bleeding during the course of bariatric surgeries. Background: Bariatric surgery is safe with a low percentage of complications compared with other abdominal surgeries. Bleeding is one of the most common complications in surgery for obesity that has the risk of being catastrophic. Methods: The study includes 8,544 cases that underwent bariatric surgery from January 2013 to March 2016 retrospectively, in 4 private institutions. Multiple demographic data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…In addition to assistance with diagnosis, endoscopy may provide therapy through a variety of mechanisms– via injection, mechanical, thermal, and topical therapies. If endoscopic treatment fails, angiography therapy or emergency surgery may be indicated[ 34 , 35 ]. The proposed algorithm for the management of early bleeding after bariatric surgery is described in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…In addition to assistance with diagnosis, endoscopy may provide therapy through a variety of mechanisms– via injection, mechanical, thermal, and topical therapies. If endoscopic treatment fails, angiography therapy or emergency surgery may be indicated[ 34 , 35 ]. The proposed algorithm for the management of early bleeding after bariatric surgery is described in Figure 2 .…”
Section: Resultsmentioning
confidence: 99%
“…Based on clinical studies, bariatric surgery is the most effective treatment for obesity 13,22 . The number of SG complications is relatively low, and with a rate of about 1.6% to 2.3%, this type of operation can be considered safe 21,23 . SG procedure is the choice of more than 70% of patients in the United States, Europe and Israel who tend to undergo obesity surgery which has been trending among various types of bariatric surgery in the past 10 to 15 years 24 .…”
Section: Discussionmentioning
confidence: 99%
“… 13 , 22 The number of SG complications is relatively low, and with a rate of about 1.6% to 2.3%, this type of operation can be considered safe. 21 , 23 SG procedure is the choice of more than 70% of patients in the United States, Europe and Israel who tend to undergo obesity surgery which has been trending among various types of bariatric surgery in the past 10 to 15 years. 24 Although bariatric surgery is safe and has many health benefits, as mentioned, there are some complications reported in patients, which nutritional deficiencies leading to clinical depression are one of the major complications in post‐operative periods.…”
Section: Discussionmentioning
confidence: 99%
“…A review of multiple reports published over more than 10 years/with a greater than 10-year observation demonstrated that the percentage of excess weight loss (%EWL) could vary from 56.7% after gastric bypass (RYGB) to 45.9% after laparoscopic adjustable gastric banding (LAGB) and 58.3% after laparoscopic sleeve gastrectomy (SG) [16]. However, bariatric procedures also pose a considerable risk of complications [17][18][19], such as anastomotic leakage [20,21], bleeding [22,23], marginal ulcer [23,24], and anastomotic stenosis [24]. In the present study, 50% (n = 110) of the patients had a preoperative BMI ≥ 43.5 ± 4.3 m 2 , corresponding to severe obesity, in the case of which surgical treatment may produce desirable outcomes.…”
Section: Discussionmentioning
confidence: 99%